2017
DOI: 10.1007/s12070-016-1047-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Radiological and Endoscopic Findings in Patients Presenting with Dysphagia

Abstract: Dysphagia is a common symptom with diverse etiology in otolaryngology. In the present study clinicopathological, radiological and endoscopic evaluation of patients was done in a tertiary care hospital in patients presenting with dysphagia. A prospective nonrandomized observational study was carried out on total of 80 cases having dysphagia during March 2015 to August 2016. In the present study, out of 80 patients, youngest case was a three years old child while oldest case was an 85 years old female. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Dysphagia is a frequent complaint of patients presenting in GI clinics [7][8][9][10]. The causes of dysphagia of esophageal origin that are identified commonly are benign and malignant strictures of esophagus, reflux esophagitis, Schatzki's ring, compression occurring externally from a malignancy, disorders of motility, scleroderma and achalasia [11][12][13][14][15][16]. In some population-based studies, the rates of prevalence of dysphagia have been reported to be 17-25% with a peak in symptoms at the age of 40-49 years for both gender [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Dysphagia is a frequent complaint of patients presenting in GI clinics [7][8][9][10]. The causes of dysphagia of esophageal origin that are identified commonly are benign and malignant strictures of esophagus, reflux esophagitis, Schatzki's ring, compression occurring externally from a malignancy, disorders of motility, scleroderma and achalasia [11][12][13][14][15][16]. In some population-based studies, the rates of prevalence of dysphagia have been reported to be 17-25% with a peak in symptoms at the age of 40-49 years for both gender [17,18].…”
Section: Discussionmentioning
confidence: 99%